Collaborative Governance Dalam Penanganan Gelandangan dan Pengemis di Kota Batam Tahun 2023 - Rotua Marbun; Yudhanto Satyagraha Adiputra; Eki Darmawan (Lembaga Pengembangan Kinerja Dosen, 2025)
In 2023, Batam City will record 550 homeless people and beggars undergoing rehabilitation. In 2024 (January-July), this number will drop significantly to 237. The aim of this research is to determine government collaboration in handling homeless people and beggars in Batam City. The method used is descriptive qualitative, there are eight informants with data collection techniques through interviews, observation and documentation. Data analysis was carried out through data reduction, data presentation, and drawing conclusions. This research uses Collaborative Governance theory from Deseve, namely Network Structure (Organizational Structure), Commitment to a Commom Purpose (Commitment to the goal), Trust Among the Participants (mutual trust between actors), the existence of Governance Certainty, Access to Authority (Access to power), Distributive Accountability (Sharing responsibility), Information Sharing (Sharing Information), Access to Resources (Access to Resources. The findings obtained are (1) Network Structure: Satpol PP carries out patrols and the Social Service supports it through the formation of a Rapid Response Team (TRC). (2) Commitment to a Common Purpose: Satpol PP and the Social Service are committed to outreach and reducing the number of Social Welfare Recipients, which is evaluated based on the budget. (3) Trust Among the Participants: collaboration between Satpol PP and the Social Service is running well thanks to open communication, regular coordination meetings, and mutual assistance. (4) There is certainty of governance: the role of Satpol PP and the Social Service is regulated in Regional Regulation No. 6 of 2002 and received support from other institutions. (5) Access to Authority: handling homeless people is regulated by Law no. 23 of 2014, with Satpol PP on patrol duty and the Social Service handling social problems through a budget supervised by the Inspectorate and BPK. (6) Distributive Accountability: The Social Service appoints the relevant OPD and forms a TRC which collaborates with Satpol PP in networking, while the TRC supports large or special activities. (7) Information Sharing: The Social Service shares the latest data and regulations in coordination meetings. (8) Access to Resources: Satpol PP and TRC have resources with a supporting budget as well as contributions from Srikandi PLN in counseling, equipment, and Pelni for the repatriation of homeless people and beggars. Therefore, researchers put forward suggestions, namely that the government should reach out more to the community and provide full assistance so that homelessness and beggars can be reduced.